The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/6902152
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of Visible Light Communication Capacity Employing Quasi-Linear Preequalization with Peak Power Limitation

Abstract: We propose quasi-linear preequalization to be used for high speed visible light communication (VLC) system. Compared with zero-forcing preequalization, this kind of preequalization method is more suitable for a real VLC experimental system with peak power limitation. We carry out simulations and experiments to test the performance of quasi-linear preequalization. With this equalizer, the 3 dB bandwidth of the system can be extended from 17 MHz to 450 MHz. We implement 2.32 Gbit/s phosphorescent white light-emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, full pre-equalization resulted in the decrease of the overall SNR when compensating for the high-frequency components of the signal, thus degrading the system performance [19] . It had been demonstrated that partial pre-equalization can address this contradictory trade-off and achieve a better system performance [20] . In the experiment, we changed the scaling factor α to adjust the ratio of partial pre-equalization.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…However, full pre-equalization resulted in the decrease of the overall SNR when compensating for the high-frequency components of the signal, thus degrading the system performance [19] . It had been demonstrated that partial pre-equalization can address this contradictory trade-off and achieve a better system performance [20] . In the experiment, we changed the scaling factor α to adjust the ratio of partial pre-equalization.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%